2013 IEEE International Symposium on Industrial Electronics 2013
DOI: 10.1109/isie.2013.6563793
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless speed control of a permanent magnet DC motor by compensating the plant nonlinearities

Abstract: Permanent magnet dc motors are popular for the simplicity of their control. Exist a few methods of sensorless speed control (SSC) of these motors. Each of these methods has its limitations that restrict its wider applicability. One of these methods uses the sensing of applied armature voltage and armature current to obtain an estimate of the motor speed, and then uses this estimate for the feedback control of the motor speed. In the microcontroller-based control of a PMDC motor, or a dc motor with separate fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…This approach is used in a wide variety of motors, not just brushed DC motors [4]. A simple yet accurate model for a brushed DC motor is based on the motor being modelled as a series resistor R, inductance L and generator which provides a back electromotive force (EMF) [5,6]…”
Section: Model-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is used in a wide variety of motors, not just brushed DC motors [4]. A simple yet accurate model for a brushed DC motor is based on the motor being modelled as a series resistor R, inductance L and generator which provides a back electromotive force (EMF) [5,6]…”
Section: Model-based Methodsmentioning
confidence: 99%
“…Interesting methods have included fuzzy algorithms [10,11], wavelets [12], genetic algorithms [13,14] and Kalman filters [15][16][17]. Saurav and Potluri [5] showed that for better accuracy the model should include mechanical factors, such as friction and any mechanical or electrical non-linearities. Speed estimation inaccuracies can be as low as 1-2% [5,18] at low PWM frequencies.…”
Section: Research Articlementioning
confidence: 99%
“…Recently, researches on sensorless speed estimation in all kinds of motors are going on [1][2][3][4]. Observer-based estimation may require dynamic system behaviours [3] and may increase the uncertainty in the estimation process. Adaptive filter based speed estimation approach was proposed earlier in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Inductive spike duration based speed estimation approach was also proposed for brushed DC motor in [14], which does not comply with DC motor operated by steady terminal voltage and also may require further error reduction technique. In some studies [15], back-EMF-based speed estimation was proposed for brushed DC motor operated with steady terminal voltage but applicability is restricted to the motor having armature size <1 cm 3 . SVM method based speed estimation for brushed permanent magnet direct current (PMDC) motor considering the commutation effect was also reported in [16], which may increase the computational burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation